A synergistic co-passivation strategy for high-performance perovskite solar cells with large open circuit voltage. Issue 35 (22nd August 2022) - Feng, Yan; Liu, Rong; Li, Fumin; Jin, Mengqi; Du, Qing; Rong, Yanjing; Hu, Hangyu; Wang, Mengxin; Li, Yu; Shen, Zhitao; Liu, Ying; Li, Huilin; et al.
Abstract : The M-QDs and OAI synergistic co-passivated perovskite film displays the reduction of defect density and charge recombination, leading to an excellent performance PSC with a high PCE of 22.01%, a large V oc of 1.20 V and remarkable stability. Abstract : Perovskite solar cells (PSCs) have shown great application potential due to their excellent performance and simple manufacturing processes. However, defects in the interior and surface of perovskite films are one of the vital issues restricting their further performance improvement. Therefore, it is imperative to reduce these defects. Here, we have developed a synergistic co-passivation strategy, which is a two-step targeted passivation (TSTP) sequentially using functional oleyl amine-coated MAPbBr3 quantum-dot (M-QD) solution for the first step and n-octylammonium iodide (OAI) solution for the second step to treat the perovskite layer, in order to minimize defects in the perovskite film. According to the morphology, structure and photoelectric property measurements of the perovskite film, it has been revealed that the grain boundaries would be caulked by M-QDs and become fuzzy due to the DMF present in the M-QD solution. Further, the film defect passivation could be realized using OAI. As a result, the optimized TSTP-based PSC achieved an excellent power conversion efficiency of 22.01% with a high open-circuit voltage of 1.20 V and exhibited remarkable stability both in air (∼25 °C at ∼30% humidity) and in an N2 environment (at 85 °C or under continuous illumination), which are much better than those of the control PSC without any post-passivation.